2018
DOI: 10.1177/0963689718817478
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Utility of p16 Immunostaining in Differentiating Cancer and HSIL from LSIL and Benign in Cervical Cells

Abstract: Cervical liquid-based cytology plays an important role in the diagnosis of cervical squamous intraepithelial lesion (SIL). However, cytological evaluation alone has a relatively low sensitive. To overcome this problem, HPV DNA testing or HPV DNA combined with cytology has been applied. HPV DNA testing significantly improved the sensitivity, but the specificity is low, especially in cancer and high-grade SIL (HSIL) cases. The aim of this study was to evaluate the diagnostic utility of p16 overexpression in cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
3
13
0
1
Order By: Relevance
“…We confirmed p16 overexpression in our series of 78 cervical tumors, as extensively described [3,14,16,21], since strong p16 expression is a proven useful surrogate biomarker for tumors with transcriptionally active HR-HPV [5]. Importantly, we found that p16 expression-and especially the cytoplasmic/nuclear p16 ratio-significantly distinguished HSIL from SCCC.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We confirmed p16 overexpression in our series of 78 cervical tumors, as extensively described [3,14,16,21], since strong p16 expression is a proven useful surrogate biomarker for tumors with transcriptionally active HR-HPV [5]. Importantly, we found that p16 expression-and especially the cytoplasmic/nuclear p16 ratio-significantly distinguished HSIL from SCCC.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are therefore evidence of the usefulness of p16 as a diagnostic biomarker between HSIL and SCCC, as previously proposed [18,19]. In fact, it has facilitated inter-observer agreement and then has improved the accuracy of traditional diagnostic methods based on histological observation in lower grade lesions [4][5][6]21,30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In conditions of inhibition / low P16 expression, there will be high expression of cancer stem cells which results in increased ability of self-renewal of cancer stem cells 16 . The sensitivity, specificity and accuracy of P16 biomarker to diagnose SCC of cervix is 96.0%, 88.2% and 91.7%, respectively 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Следовательно, функциональная инактивация pRB приводит к рефлекторной активации p16, экспрессия которого в низких концентрациях наблюдается в здоровых клетках, в то время как при HSIL и РШМ наблюдается гиперэкспрессия p16. Данный феномен используется в качестве надежного индикатора персистенции высокоонкогенных типов ВПЧ [21].…”
Section: припутневич татьянаunclassified